Cold, cold bones [compact disc, unabridged] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2022)
Winter has come to North Carolina and temporarily idle forensic anthropologist Tempe Brennan is content to dote on her daughter Katy. But when mother and daughter meet at Tempe's place one night for dinner, they find a box on the back porch. Inside: a very fresh human eyeball. GPS coordinates etched into the eyeball lead to a Benedictine Monastery where an equally macabre discovery awaits. Soon after, Tempe examines a mummified corpse in a state park, and her anxiety deepens. There seems to be no pattern to these random killings, except that each mimics in some way a killing that a younger Tempe witnessed, analyzed, or barely escaped.